Information Technology Governance Audit Using COBIT Framework 2019 (Case Study: Mandiri University) - Hanifa Nurcahya; Erwan Setiawan; Budi Permana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Mandiri University is an educational institution that has used information technology assistance in a series of work procedures in its business activities. Utilization of IT as one of the factors that support the achievement of the organization's vision and mission. Where it must be managed optimally considering that Mandiri University is a potential campus if the operational process is really carried out optimally. In order to achieve the expected results, it is necessary to conduct an audit that examines the current state of governance, as well as the expected governance, so that gaps or gaps are known between the two. Then provide recommendations for improvement proposals so that Mandiri University can maximize the use of IT in the activities carried out.